The case against socialism - Paul, Rand; Paul, Kelley (Broadside Books, an imprint of HarperCollinsPublishers, 2019)
"Rand Paul, U.S. senator for Kentucky and America's most prominent libertarian, makes a case against socialist ideology, showing the impact of its deadly legacy and the threat of its new rise in America"--